Optical Properties of Mixed ZnO: Fe2O3 Grown via Pulsed laser deposition - Hanfoosh, S. M.; Hassan, N. K. (Iraqi Journal of Science, 2019)
In this study, mixing of zinc oxide (ZnO) nanoparticles with iron oxide(Fe2O3) at (0, 0.1, 0.3, 0.5 and 1)%wt., are deposited on glass substrates by pulsed laser deposition (PLD) technique for study characterization ZnO:Fe2O3 as solar cell electrode. The profound effect of mixed film on the structural and optical of ZnO: Fe2O3 thin films was observed. Meanwhile, the films have polycrystalline Hexagonal structures for ZnO, Rhombohedra and cubic structure for Fe2O3, and as indicated by the X-ray diffraction patterns of the films. The mean crystallite size of ZnO increase with increasing mixed ratio. The direct energy gap (Eg) of ZnO is 3.36 eV and decreasing with increasing mixed ratio.